2013
DOI: 10.1109/lsp.2013.2281607
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Early Mode Decision Technique for View Synthesis Prediction-Enhanced Multiview Video Coding

Abstract: Abstract-View synthesis prediction (VSP) is a coding mode that predicts video blocks from synthesised frames. It is particularly useful in a multi-camera setup with large inter-camera distances. Adding a VSP-based SKIP mode to a standard Multiview Video Coding (MVC) framework improves the rate-distortion (RD) performance but increases the time complexity of the encoder. This letter proposes an early mode decision technique for VSP SKIP-enhanced MVC. Our method uses the correlation between the RD costs of the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It was found that using the proposed technique, over 33% of the encoding time can be reduced without a noticeable degradation in the RD performance. The results of this contribution were published in [35]. VSP modes are expected to be included in upcoming video coding standards such as 3D-AVC [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that using the proposed technique, over 33% of the encoding time can be reduced without a noticeable degradation in the RD performance. The results of this contribution were published in [35]. VSP modes are expected to be included in upcoming video coding standards such as 3D-AVC [49].…”
Section: Discussionmentioning
confidence: 99%
“…• An early mode decision method for View Synthesis Prediction mode enhanced multiview video coding [35]. The method exploits the bayesian decision rule to minimize the number of candidate modes checked during…”
Section: Contributions Of the Thesismentioning
confidence: 99%
“…By combining the MVC methods in [19][20][21] with PDV-DE, a novel complexity reduction technique can be derived. The correlation of rate distortion (RD) costs among inter-views in SKIP mode are studied and used to reduce the computational complexity of MVC in [23]. Khattak et al have used the correlation between the RD costs of the SKIP mode in neighboring views and Bayesian decision theory to reduce the number of candidate coding modes for a given MB [24].…”
Section: Introductionmentioning
confidence: 99%
“…Computer vision is a discipline that studies how to make computers "see" like humans. In detail, it uses cameras and computers to replace the human eye, enabling the computer to achieve the functions of segmenting, classifying, identifying, tracking, and discriminating decisions like the human visual system [2,3]. On the basis of image and signal processing technology, probability statistical analysis, computational geometry, and neural network technology, the computer and its related equipment carry out biological vision simulation [4], with the purpose of enabling it to recognize three-dimensional environmental information through two-dimensional images.…”
mentioning
confidence: 99%